'Big Mac Affordability' and real-income inequality across countries. Issue 16 (19th September 2020) - Gharehgozli, Orkideh; Atal, Vidya
ABSTRACT: Using the Big Mac Index and focusing on the deciles of the income distribution, we produce a descriptive study of real-income inequality from households in 29 countries and for period 2000 to 2013. Using daily Big Mac Affordability (BMA), we rank and show differences in the living standards and the purchasing power of individuals belonging to different income deciles in these countries. We also provide a multidimensional Big Mac real-income inequality analysis by looking at Coefficient of Variation as well as the share of bottom to top decile BMA (as a measure of dispersion) across countries.